COST ACCOUNTING IN GREAT BRITAIN. - Noble, H. S. (The Accounting Review, 1929)
The article focuses on cost accounting in Great Britain. Institute of Cost and Works Accountants was organized in 1919 with its headquarters in the city of London, with local chapters in London, Liverpool, Manchester, Sheffield, Birmingham and other centres. It publishes a periodical giving articles with aspects of cost accounting and news of the chapter activities. It sets examinations which must be passed as a prerequisite to membership. The purpose to be served by cost accounting include, statistical, economic, manufacturing and administrative. The extent of analysis, the technique of the system and the intricacy of its operation are all to be dependent upon the executive's use of the cost reports. Cost accounting is also considered as a partial solution to labor difficulties. It is suggested that accurate cost thinking on the part of labor and capital will give both parties a similar point of view and lead to co-operation. There is a new appreciation of the utility of cost accounting, in the light of present industrial condition in Great Britain.